2019
DOI: 10.1002/sdtp.13394
|View full text |Cite
|
Sign up to set email alerts
|

8.4: Invited Paper: Oxide devices for displays and low power electronics

Abstract: Oxide semiconductors have been envisaged to find applications in flexible electronics in daily life such as wearable electronic gadgets to offer novel user experiences. However, there are still several bottlenecks to overcome in order to realise this goal, especially the lack of oxide‐semiconductor components fast enough for wireless communications, low power oxide transistors, and high‐performance p‐type oxide semiconductors for complementary circuits. Here we review our recent work to address these problems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The competitive superiority of a-IGZO TFTs is based on the fact that they can offer high carrier mobility, high optical transparency, and low off-state leakage compared with traditional Si-based TFTs [1][2][3], and their manufacturing cost is lower than that of lowtemperature polycrystalline silicon (LTPS) TFTs with large-area uniformity [4,5]. However, due to the high density of subgap defects existing in the bandgap of a-IGZO, the carrier mobility (µ FE ) and electrical stability are insufficient for advanced display applications such as AR/VR displays, flexible logic circuits, three-dimensional (3D) displays, and low-power mobile devices [6][7][8][9]. It has been reported that the subgap states mainly originate from oxygen vacancy-related defects induced by the structural disorder in a-IGZO [10], which affects the electrical properties and stability of TFTs by trapping electrons or holes in the channel layer and device interfacial region under gate bias stress, light illumination, and thermal stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…The competitive superiority of a-IGZO TFTs is based on the fact that they can offer high carrier mobility, high optical transparency, and low off-state leakage compared with traditional Si-based TFTs [1][2][3], and their manufacturing cost is lower than that of lowtemperature polycrystalline silicon (LTPS) TFTs with large-area uniformity [4,5]. However, due to the high density of subgap defects existing in the bandgap of a-IGZO, the carrier mobility (µ FE ) and electrical stability are insufficient for advanced display applications such as AR/VR displays, flexible logic circuits, three-dimensional (3D) displays, and low-power mobile devices [6][7][8][9]. It has been reported that the subgap states mainly originate from oxygen vacancy-related defects induced by the structural disorder in a-IGZO [10], which affects the electrical properties and stability of TFTs by trapping electrons or holes in the channel layer and device interfacial region under gate bias stress, light illumination, and thermal stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…The usual ways of depositing a gate dielectric are vacuum processes such as plasma-enhanced chemical vapor deposition (PECVD), sputtering, and atomic layer deposition (ALD). , The deposition of a thin gate dielectric is one way to decrease the operating voltage of a TFT. For a thin high-dielectric gate insulator, aluminum anodic oxidation was applied to obtain an IGZO TFT with a 1 V operation voltage. , …”
Section: Introductionmentioning
confidence: 99%